PENGARUH PENGGUNAAN SILASE PAKAN KOMPLIT BERBAHAN ECENG GONDOK TERHADAP KECERNAAN PROTEIN PADA DOMBA - L Hanun; A Muktiani; L K Nuswantara (Universitas Wahid Hasyim, 2019)
This study aims to determine the effect of fedding a complete ration of silage made from water hyacinth on concentration of ammonia rumen, total protein of rumen fluid and protein digestibility. Fifteen rams with average body weight of 19 ± 3.98 kg used on this research. The experiment was arranged in 3x5 randomized completed design. There treatment were T1= concentrate and elephant grass, T2= complete feed silage contained water hyacinth without L. plantarum starter addition, and T3= complete ration silage contained water hyacinth added with L. plantarum. Ration was formulated by isoenergy and isoprotein feed (CP 13%, TDN 65%). Feed treatment was given for 12 weeks. The results showed that the consentration of ammonia rumen was different (P0,05). Concentration of ammonia rumen of T1, T2 and T3 as follows: 2,53, 2,04, 1,80 mM. Total protein of rumen fluid and protein digestibility ranged by 295,70-381,04 mg/g and 75,00-77,29%. The conclusions of this study were the provision of complete feeding silage either without or with the addition of L. plantarum starter to produce the same digestible protein as conventional ration (concentrate and elephant grass). Keywords : silage, water hyacinth, protein, digestibility, sheep.